The co-occurrence of anthracosis with interstitial lung disease - Zhai, LiYing; Yu, WenCheng (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Objective：Anthracosis is defined as deposition of black pigments in the bronchial mucosa or lung parenchyma. The aim of this study was to investigate the clinical features of patients with coexisting anthracosis and interstitial lung diseases (ILDs). Methods: A total of 335 ILDs patients who underwent bronchoscopy at the affiliated hospital of Qingdao University were included in our study. We enrolled 71 patients who diagnosed with anthracosis by bronchoscopy. The clinical presentations, radiographic features, and bronchoscopic findings of the patients were reviewed.  Results: Compared with the non-anthracosis group, biomass exposure (48, 67.6% vs. 153, 53.9%, p=0.041), the median pressure of carbon dioxide before six-minute test (42.00 mmHg vs. 40.00 mmHg, P=0.001), the mean peak expiratory flow (115.21±23.55 %predicted vs. 104.20±26.17%predicted, P=0.048), the mean level of triglyceride (1.79±1.27 mmol/L vs. 1.51±0.74 mmol/L，P=0.034) were significantly increased and the mean oxygen saturation after six-minute test (95.49±2.72% vs. 96.56±1.27%, P=0.028), the mean cardiac ejection fraction (61.22±2.07% vs.62.08±2.89%, P=0.019) were significantly decreased in the anthracosis group. However, we didn’t find significant difference between the two groups in lymph node calcification (p=0.620) and lymphadenectasis (p=0.440).Conclusions: Biomass smoke is a risk factor for anthracosis. Anthracosis produce a bad effect on the oxygenation, cardiac function and lipid metabolism in ILDs patients. The ILDs patients should decrease the exposure of biomass.